Brain death: optimizing support of the traumatic brain injury patient awaiting organ procurement. Issue 2 (April 2020) - Souter, Michael J.; Kirschen, Matthew
Abstract : Purpose of review: Increasing numbers of deaths on the transplant waiting list is associated with an expanding supply–demand deficit in transplantable organs. There is consequent interest in reviewing both donor eligibility after death from traumatic brain injury, and subsequent management, to minimize perimortem insult to donatable organs. Recent findings: Recipient outcomes are not worsened when transplanting organs from donors who were declared dead after traumatic brain injury. Protocolized donor management improves overall organ procurement rates and subsequent organ function. Longer periods of active management (up to 48 h) are associated with improved outcomes in renal, lung, and heart transplantation. Several empirically derived interventions have been shown to be ineffective, but there are increasing numbers of structured trials being performed, offering the possibility of improving transplant numbers and recipient outcomes. Summary: New studies have questioned previous considerations of donor eligibility, demonstrating the ability to use donated organs from a wider pool of possible donors, with less exclusion for associated injury or comorbid conditions. There are identifiable benefits from improved donor resuscitation and bundled treatment approaches, provoking systematic assessments of effect and new clinical trials in previously overlooked areas of clinical intervention.